Evidence of silicic acid leakage to the tropical Atlantic via Antarctic Intermediate Water during Marine Isotope Stage 4 - Griffiths, JD; Barker, S; Hendry, KR; Thornalley, DJR; Van De Flierdt, T; Hall, IR; Anderson, RF (2013)
Antarctic Intermediate Water (AAIW) and Subantarctic Mode Water (SAMW) are the main conduits for the supply of dissolved silicon (silicic acid) from the deep Southern Ocean (SO) to the low-latitude surface ocean and therefore have an important control on low-latitude diatom productivity. Enhanced supply of silicic acid by AAIW (and SAMW) during glacial periods may have enabled tropical diatoms to outcompete carbonate-producing phytoplankton, decreasing the relative export of inorganic to organic carbon to the deep ocean and lowering atmospheric pCO2. This mechanism is known as the "silicic acid leakage hypothesis" (SALH). Here we present records of neodymium and silicon isotopes from the western tropical Atlantic that provide the first direct evidence of increased silicic acid leakage from the Southern Ocean to the tropical Atlantic within AAIW during glacial Marine Isotope Stage 4 (∼60-70 ka). This leakage was approximately coeval with enhanced diatom export in the NW Atlantic and across the eastern equatorial Atlantic and provides support for the SALH as a contributor to CO2 drawdown during full glacial development. © 2013. American Geophysical Union. All Rights Reserved.